Side by side: neoliberalism and crime control in post-apartheid South Africa - Gordon, Diana R. (Social justice, 2001)
The dependence of South Africa on foreign investment and international donor organizations—probably inevitable in the era of globalization—appears to be likely to contribute to aggressive law enforcement and strict penal sanctions for the immediate future. Whether or not crime has increased after the apartheid era, it is clear that there is too much of it and that violence has moved into the white affluent neighborhoods as well. Globalization has relayed the importance of the connection between an investor's expectation of a business environment that is conducive to profit and a country's commitment to law enforcement.